2011
DOI: 10.1158/1078-0432.ccr-10-3381
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Differentiation-1 as a Novel Prognostic Factor in NSCLC Patients with Adenocarcinoma Histology and Its Potential Contribution to Therapy Resistance

Abstract: Purpose: High inhibitor of differentiation-1 (Id1) levels have been found in some tumor types. We aimed to study Id1 levels and their prognostic impact in a large series of stages I to IV non-small cell lung cancer (NSCLC) patients. Experiments in cell lines and cells derived from malignant pleural effusions (MPE) were also carried out.Experimental Design: A total of 346 NSCLC samples (three different cohorts), including 65 matched nonmalignant tissues, were evaluated for Id1 expression by using immunohistoche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 34 publications
(39 reference statements)
7
49
0
Order By: Relevance
“…In agreement with Ponz-Sarvis et al, 37 our analyses showed a significantly higher expression of Id-1 protein in ADC tissue compared with normal lung tissue. Unexpectedly, Bhattacharya et al 33 showed significantly lower Id-1 mRNA expression levels in ADC and matched normal but no IHC staining was performed to confirm the 34 conducted an investigation in malignant cell lines from small cell lung cancer and found that Id-1 gene was up-regulated.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with Ponz-Sarvis et al, 37 our analyses showed a significantly higher expression of Id-1 protein in ADC tissue compared with normal lung tissue. Unexpectedly, Bhattacharya et al 33 showed significantly lower Id-1 mRNA expression levels in ADC and matched normal but no IHC staining was performed to confirm the 34 conducted an investigation in malignant cell lines from small cell lung cancer and found that Id-1 gene was up-regulated.…”
supporting
confidence: 93%
“…As we observed that the majority of tumor cells expressed nuclear Ids, we applied a modified H-score, where the extension of nuclear intensity of staining was scored as percentage of positive cells and the intensity of staining was assessed compared with a known external positive control. Actually, there has been uncertainty about staining for Ids and its relationship with different histological type 33,34,37,38 ) and how best to record staining for Ids. Yang et al 42 employed a semi-quantitative score in breast carcinoma classified by plus into four groups: þ, 0-10%; þþ, 10-20%; þþþ, 20-30%; þþþþ, 30-40%.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs that stimulate ROS have been shown to sensitize tumors to first-line agents (Wondrak, 2009). Moreover, using genetic approaches to down-regulate Id1 expression has re-sensitized aggressive cancer cells to treatments with first-line therapies (Hu et al, 2009; Ponz-Sarvise et al, 2011). In breast cancer cells, where CBD is effective at downregulating Id1 expression, CBD enhanced the activity of the first-line agent, paclitaxel (Ward et al, 2014).…”
Section: Cannabinoids In Combination With First-line Therapiesmentioning
confidence: 99%
“…Reducing SDS-PAGE was performed and samples were blotted onto a PVDF-membrane. p62 (MBL), CDC2, pCDC2, PTEN, Cleaved caspase3, LC3, ATF4, AKT, pAKT (Cell signaling), E-cadherin, N-cadherin, Vimentin (Abcam) and ID1 [24] antibodies were tested. Loading control was a rabbit anti-GAPDH (Abcam) and anti-beta actin (Sigma-Aldrich).…”
Section: Protein Expression Analysismentioning
confidence: 99%